Clinical practice guidelines : directions for a new program - Field, Marilyn J. (Marilyn Jane); Lohr, Kathleen N., 1941- (IOM publication, 1990)
The Alberta clinical practice guidelines program is supporting appropriate, effective and quality medical care in Alberta through promotion, development and implementation of evidence-based clinical practice guidelines.